"The Harsh Reality: Unraveling the Effects of Childhood Exposure to Violence" (International Journal of Food and Nutritional Sciences, 2022)
To improve children's health and wellbeing, there is a need to address the widespread violence against children. Children are vulnerable to all types of violence, including physical, psychological, sexual, and others. Stress, anxiety, and depression in children are all known risk factors. Domestic violence, school violence, and community violence are the types of violence that have been linked to negative psychological effects. Children that are exposed to violent environments have drastically altered psychophysiological and behavioral functioning. The purpose of this study was to evaluate the amount of anxiety and tension experienced by children exposed to violence, as well as the prevalence and effects of violence on children.For this study, a quantitative research strategy and a descriptive research design were chosen. The 100 school-age participants in the current study were chosen using the snowball sampling technique. To get the information, a systematic questionnaire was used. Part I of the questionnaire covered demographic information, while Part II included structured questions to gauge how frequently people are exposed to violence.